STUDI AYAT-AYAT TENTANG MEMILIH PEMIMPIN NON-MUSLIM PERSPEKTIF MUFASIR INDONESIA - Irsad, Muhammad (Nurani, 2017)
Study Verses About Choosing Non-Muslim Leaders Perspective Interpreter in Indonesia". Anxiety due to the phenomenon in the country on suspicion of desecration of the Koran which became national tensions underlying the researchers raised the theme above. Indonesian Islamic community with a wide range of understanding and attitude, while it goes not reaped consensus on these issues. This study tried to take photos of the national uproar from the perspective angle interpreter Indonesia. This research is a library research, which makes al-Ibriz, Al-Azhar, and Al-Misbah as a primary source in this study. This study uses a comparative approach (muqarin) in approaching the issues discussed. This study aimed to describe the interpretation of passages about choose non-Muslim leaders in Indonesia commentators perspective and provide legal clarity choose non-Muslim leaders in Indonesia.